Awareness of the health care worker’s vaccination 2024: A Systemic Review - Ahmed Muteb Muriaa Al-Obaidi; Muteb Ali Ibrahim Koriri; Hussain Ahmed Mohammed Kariri; Hakem Motlak Alenzy; Sami Mohammed Saed Alghamdi; Maram Abdulrahim Misfer Alghamdi; Suliman Mohammed Saed Alghamdi; Fares Saed Salah Alzahrani; Zakiali Mohammad Alamer; Azizah Ahmad Banafi; et al. (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background: Healthcare workers (HCW) awareness toward vaccines influences patient and community vaccine decision making. In an era of rising vaccine hesitancy and understanding HCW vaccine awareness is critical. The of health care worker’s Vaccination Experts recommended that efforts be made to improve healthcare workers’ awareness, knowledge and beliefs about vaccines, and their attitudes towards them, to increase vaccination coverage. While most health care workers vaccinate according to the recommended schedule, this success is challenged by individuals and groups who delay or refuse vaccines. Despite evidence demonstrating the benefits of vaccination for health care workers, individuals, populations and health systems and society in general, vaccine hesitancy still remains a key factor influencing vaccine uptake, sometimes leading to outbreaks of vaccine-preventable diseases. Aim of the study: This systematic review aims to review awareness among HCW vaccine 2024 Methods: We searched multiple databases for peer-reviewed studies published in English that awareness vaccine acceptance and/or uptake in health care workers and conducted a systematic search in four electronic databases for studies published between February 2020 and June 2024. We included studies conducted in developed countries that used statistical methods to relate or associate the variables included in our research question. Two independent reviewers verified that the studies met the inclusion criteria, assessed the quality of the studies and extracted their relevant characteristics. The data were descriptively analyzed. Results: he searches produced studies after removing duplicates; high numbers of studies were excluded because the interventions were not applied to health care workers. The search ended with 7 studies that met our pre-specified criteria and were included in the review. In total, 802 records of papers were identified from the search of the literature. Based on a title review, 494 records were excluded. Conclusion: Tailored interventions are needed to bolster awareness in the vaccination, maximize vaccine uptake, and increase vaccine access to close the gaps between acceptance and uptake especially among key health care worker’s residing in regions with low rates of acceptance and uptake. We that there is a low vaccine uptake rate among our study health care worker’s, considering that the barriers most commonly chosen by participants are solvable with health education and campaigns oriented towards delivering facts about the vaccine and dispelling misinformation .